Bactris guineensis, an underutilized Costa Rican palm fruit: juice processing and its nutritional profile - Cortés-Herrera, Carolina (2024)
Introduction. Bactris guineensis is a crop that produces visually appealing fruits resembling purple-black grapes with round seeds. This palm species naturally thrives in the lowland regions of tropical America. However, limited information available about this fruit. Objective. To investigate the nutritional composition, bioactive compound content, antioxidant capacity, and aroma profile of the huiscoyol fruit grown in Costa Rica, as well as to evaluate the effects of juice processing (enzymatic maceration and thermal treatment) on its bioactive compounds and antioxidant capacity. Materials and methods. Fruits were collected from randomly selected palms and bunches in Guanacaste Conservation Area, specifically in Palo Verde and Cañas, during peak harvest years (2007, 2011, 2014, and 2016). Nutritional composition, bioactive compound content, antioxidant capacity, and aroma and polyphenol profiles were analyzed. Juices were prepared using thermal treatment, enzymatic maceration, and a combination of both methods. The bioactive compound content and antioxidant capacity were assessed following each treatment. Results. Huiscoyol fruit exhibited high fiber content [7.3 ± 2.5 g per 100 g of fresh weight (fw)], and significant potassium content (307 ± 98 mg per 100 g fw). Anthocyanin levels ranged from 28.3 to 47.9 mg per 100 g fw, with cyanidin-3-O-rutinoside as the predominant compound. Total polyphenol content varied between 219 and 1,013 mg gallic acid equivalents per 100 g fw. Vitamin C content reached a maximum of 48 mg per 100 g fw. Antioxidant capacity, as measured by H-ORAC, ranged from 6,690 to 14,688 µmol Trolox equivalents per 100 g fw. Enzymatic maceration and thermal treatments applied to the juice did not significantly affect the bioactive compounds content or antioxidant activity (p > 0.05). Conclusion. Huiscoyol fruit demonstrate nutritional and antioxidant potential, making it promising ingredient for funtional beverages. Its bioactive components, such as polyphenols and anthocyanins, showed remarkable stability under thermal and enzymatic processing conditions.